Predictors of Recurrent Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The results of 14 published reports were analyzed to evaluate the strength of association between proposed risk factors and recurrence of febrile seizures in a metaanalytic review from the Departments of Pediatrics and Epidemiology and Public Health, Yale University School of Medicine, New Haven, CT; Montefiore Medical Center, The Albert Einstein College of Medicine, Bronx, New York; and Columbia University College of Physicians and Surgeons, New York, NY.